Quantitative Evaluation of Fire and EMS Mobilization Times - Upson, Robert; Notarianni, Kathy A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
1
Study Questions and Research Methods -- Recruiting Participants -- Data Collection -- Data Analysis -- Primary Findings -- Conclusions -- Future Study Questions.
Keywords: Statistics; Numerical analysis; Statistics; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Operations Research, Management Science; Numerical Analysis